Colonization of Oryza Sativa Roots by Plant Growth-Promoting Rhizobacterium, Bacillus Sphaericus UPMB10 and Subsequent Inoculant Formulation - Pakirisamy, Premalatha (2006)
The Bacillus sphaericus UPMB10 plant growth-promoting strain was selected for colonization and inoculant formulation studies. The UPMB10 strain is a Gram positive, endospore forming bacteria. The biochemical assay results showed that this strain was able to hydrolyze complex carbon source (potato starch) but did not utilize simple sugars. The UPMB10 strain was able to grow in the presence of 10 µg mL-1 of the antibiotic streptomycin and 10U of bacitracin which may be an important inherent characteristic in the competitiveness of this plant growth-promoting rhizobacterium. The results of the in vitro colonization study showed that B. sphaericus strain UPMB10 could successfully proliferate on and colonize the roots of Oryza sativa L. MR220 for up to 28 days after inoculation. Enumeration of bacteria colonizing the rice root indicated that the UPMB10 strain colonized both the rhizoplane and the root interiors at up to 108 and 104 cfu g-1 root tissue, respectively. The production of root cell wall degrading enzymes, cellulase and pectinase, by this strain may have facilitated cellular entry. Scanning electron microscopy of colonization showed dense colonization at areas rich in root exudates specifically the elongation zone, junction of lateral roots and junctions of epidermal cells for up to 21 days. Clusters of microcolonies formed a mucigel within the mucilaginous sheath of the root. Colonies were also seen colonizing beneath what could possibly be the epidermal cuticle of the roots, especially in the relatively older primary roots. The colonization of the rice roots by this strain displayed adhesion structures which attached the cells with the root surface of rice and between each other. The process of root colonization also elicited a varying pattern of bacterial morphology during temporal colonization of rice roots. Normal rods of this strain were sized 0.5 – 0.6 µm x 1.5 – 1.9 µm. Some colonies of cells appeared rounder and fatter (0.9 – 1.1 µm x 1.3 – 1.8 µm) with widths twice that of the normal rods. Results also showed colonies elongating (length 5.3 – 6.2 µm) in readiness for cell replication possibly as a result of receiving sufficient nutrients from the colonized sites on the roots. The UPMB10 strain was successfully tagged with the green fluorescent protein (GFP) marker in the plasmid specifically constructed for this study (pSV101gfp3) by electroporation. The presence of GFP was confirmed by PCR, SDS-PAGE and Western blotting. The fluorescence signal of the transformants however, was too weak to be used to follow colonization on roots in non-sterile environments.